Probabilistische Szenenmodelle für die Luftbildauswertung - Bauer, Alexander (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2013)
The interpretation of aerial and satellite imagery requires significant experience and expert knowledge and therefore is mainly performed by professional image interpreters. So far, automatic methods are not able to provide comparable results but they can be used to support the manual image interpretation process. This work shows how the benefits of manual and automatic image interpretation can be adequately combined in an interactive image interpretation system.